2021
DOI: 10.7554/elife.69161
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neural progenitor cells and their progeny reveals long distance migration in the developing octopus brain

Abstract: Cephalopods have evolved nervous systems that parallel the complexity of mammalian brains in terms of neuronal numbers and richness in behavioral output. How the cephalopod brain develops has only been described at the morphological level, and it remains unclear where the progenitor cells are located and what molecular factors drive neurogenesis. Using histological techniques, we located dividing cells, neural progenitors and postmitotic neurons in Octopus vulgaris embryos. Our results indicate that an importa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 137 publications
(211 reference statements)
9
42
0
Order By: Relevance
“…However, no pseudostratification of the lateral lips has been described. Cephalopod central nervous system development may more closely resemble neurogenesis found in other invertebrates or molluscs (Deryckere et al, 2021;Marthy, 1987).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, no pseudostratification of the lateral lips has been described. Cephalopod central nervous system development may more closely resemble neurogenesis found in other invertebrates or molluscs (Deryckere et al, 2021;Marthy, 1987).…”
Section: Discussionmentioning
confidence: 92%
“…Although pseudostratified neurogenesis is found in the cephalopod retina, there is little evidence that the cell biology of chordal or central nervous system neurogenesis is similar. It has been reported that cells migrate from the lateral lip in the cephalopod embryo to regions within the brain (Deryckere et al, 2021). However, no pseudostratification of the lateral lips has been described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations